Atlas of nerve conduction studies and electromyography - Leis, A. Arturo; Schenk, Michael P. (Oxford University Press, 2013)
Beautifully and lavishly illustrated, Atlas of Nerve Conduction Studies and Electromyography demystifies the major conditions affecting peripheral nerves and provides electrodiagnostic strategies for confirming suspected lesions of the peripheral nervous system. Building on the success of the landmark Atlas of Electromyography, this new text is divided into sections based on the major peripheral nerves. It contains detailed illustrations of each nerve along with a discussion of its anatomy, followed by a thorough outline of the clinical conditions and entrapment syndromes that affect the nerve.